RONs Revisited: General Approach to Model Reconfigurable Object Nets based on Algebraic High-Level Nets - Ermel, Claudia; Shareef, Sarkaft; Fischer, Winzent (Electronic Communications of the EASST, 2011)
Reconfigurable Object Nets (RONs) have been implemented in ourgroup to support the visual specification of controlled rule-based transformationsof marked place/transition (P/T) nets. RONs are high-level nets (system nets) withtwo types of tokens: object nets (P/T nets) and net transformation rules. System nettransitions can be of different types to fire object net transitions, move object netsthrough the system net, or to apply a net transformation rule to an object net. Thedisadvantage of the RON approach and tool is the limitation of object nets to P/Tnets and the limitation of the underlying semantics of RONs due to the fixed typesfor system net transitions. Often, a more general approach is preferred where thetype of object nets and the behavior of reconfigurations may be defined in a moreflexible way. In this paper, we propose to use Algebraic High-Level nets with individualtokens (AHLI nets) as system nets. In this more general approach, tokensmay be any type of Petri nets, defined by the corresponding algebraic signature andalgebra. To support this general approach, a development environment for AHLInets is currently implemented which allows the user to edit and simulate AHLI nets.We present the formalization of RONs as special AHLI nets and describe the currentstate of the AHLI net tool environment.